A similarity‐based cross‐language comparison of basicness and demarcation of "blue" terms. Issue 3 (9th August 2016) - Bimler, David; Uusküla, Mari
Abstract: To investigate linguistic and perceptual boundaries within the "blue" region of the color gamut, we analyzed sorting data from speakers of six languages who sorted color stimuli by similarity. Two of these languages, Russian and Italian, are thought to have a separate basic color term and category for "light blue, " distinguishing it from "blue, " and the third was English, which lacks this distinction. There has been less study of the possible basicness of "light blue" terms in the other three languages: Lithuanian and Estonian (both spoken in Baltic states) and Udmurt (a linguistic enclave in North Russia). Sorting data from each sample of speakers were analyzed with principal component analysis and multidimensional scaling, reducing them to a pattern of interstimulus similarities. In addition, color‐naming data were collected for five of the languages and confirmed that sorting responses were not simply a reflection of the words used by subjects to label the stimuli. A "clustering index" was created, quantifying the extent of light/dark blue separation and the strength of any category boundary between them; this was low for English‐language participants but high for Russian and Italian. Udmurt and Lithuanian values were also high, whereas Estonian responses were closer to English. Thus, when clustering of blue stimuli is used as an additional indicator of basicness, the results are compatible with earlier evidence that "light blue" is a separate basic color category in Russian and Italian, and further indicate that light blue terms are basic in Udmurt and Lithuanian, but not Estonian. It may be that "blue" categories are especially susceptible to splitting into two under the influence of linguistic contact. © 2016 Wiley Periodicals, Inc. Col Res Appl, 42, 362–377, 2017